2017
DOI: 10.9778/cmajo.20170047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Fort McMurray wildfires on the health of evacuated workers: follow-up of 2 cohorts

Abstract: Background: Wildfire engulfed Fort McMurray, Alberta on May 3, 2016, leading to a total evacuation. Access to 2 active cohorts allowed us to rapidly assess health effects in those evacuated. Methods:People working in Fort McMurray who had been recruited before the fire for 2 occupational health cohort studies completed a questionnaire (online or via telephone) 3-26 weeks after evacuation. The questionnaire asked about respiratory and mental health and experiences since the fire. Results:Of the 129 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The second source of information was a pilot study set up to investigate occupational injuries in interprovincial workers in and around Fort McMurray, the hub of Alberta's oil and gas industry . Workers were recruited face‐to‐face from a number of sources including a pre‐employment/placement clinic, the hospital emergency room (used as a walk‐in clinic by workers in camps), through a one‐day safety training held daily by the local technical college and through a social club frequented by those from NL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second source of information was a pilot study set up to investigate occupational injuries in interprovincial workers in and around Fort McMurray, the hub of Alberta's oil and gas industry . Workers were recruited face‐to‐face from a number of sources including a pre‐employment/placement clinic, the hospital emergency room (used as a walk‐in clinic by workers in camps), through a one‐day safety training held daily by the local technical college and through a social club frequented by those from NL.…”
Section: Methodsmentioning
confidence: 99%
“…No one was recruited through an employer and the name of the employer was not asked in order that respondents could talk freely about unreported injuries. As has been described elsewhere the study was curtailed soon after recruitment by the outbreak of a wildfire in May 2016 which led to the total evacuation of the 80 000 in the town‐site and some 20 000 from surrounding work camps. As a result, prospective data collection on injuries was not possible but information on the most recent injury in Alberta had been collected during the recruitment interview.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 is a flowchart summarizing our search process and outcomes. This review found 60 articles that met the inclusion criteria [13,14,16,17,19,20,22,23,. Three other articles were obtained from review of relevant in-text citations during data abstraction [18,78,79].…”
Section: Outcome Of Literature Searchmentioning
confidence: 99%
“…Wildfires destroy homes and workplaces, displace victims, and impact numerous medical conditions such as chronic obstructive pulmonary disease (COPD), asthma, and mental health [10][11][12]. Studies have found higher rates post-wildfire of hypertension, gastrointestinal disorders, diabetes, and COPD and asthma exacerbation, along with various psychiatric conditions, including mood and anxiety disorders [11][12][13][14][15]. The impact of wildfires on the survivors' mental health has been found in both the adult and pediatric population, with children and adolescents also experiencing higher rates of mood and anxiety disorders post-wildfire [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Significant mental health problems associated with wildfire disasters have been documented. For example, a study of Fort McMurray residents following the Horse River fire showed increased incidences of anxiety, depression, and suicidal thoughts (Cherry and Haynes 2017;Brown et al 2019). With predicted increases in future fire activity and a growing population, we may very well expect that public health problems, health care costs, health expenditures, and mortalities associated with wildfire may rise in the future.…”
Section: Healthmentioning
confidence: 99%